Assessment of an Orthopaedic Templating Software Package for Cemented Total Hip Arthroplasty - Newman, Michael; Shaw, Grant; Kane, Timothy (The Journal of Hip Surgery, 2019)
The main aim of this article was to assess a large, multisurgeon dataset of cemented total hip arthroplasties that had been templated using software. This assessment compared preoperative templated predictions with what was implanted with regard to (1) femoral prosthesis size, (2) offset, and (3) acetabular cup size. A database of total hip arthroplasties performed by four surgeons between the dates November 7, 2014 and October 31, 2017 was interrogated. The data was refined so that only primary cemented collarless polished tapered stem hip arthroplasties, fully templated on a correctly calibrated pelvic radiograph, were included. This provided 354 cases. The predicted software template was compared with actual implanted component sizes. With regard to the femoral stem, the software was exactly correct in 70.9% and accurate to within one size in 96.89% of cases. With regard to the femoral offset, the software was exactly correct in 87.01% and accurate to within one size in 99.72% of cases. With regard to the acetabular cup size, the software was exactly correct in 61.3% and accurate to within +/− 2 mm in 87.29% of cases. Templating software offers an accurate prediction of the femoral prosthesis size and offset, as well as acetabular cup size. Preoperative insight into likely component sizes and offset provides the operating surgeon with many benefits; templating the pelvic radiograph is a method of cognitive rehearsal, provides insight into potentially challenging aspects of the upcoming surgery, may highlight intraoperative issues where there is a large intraoperative deviation from what is templated, and enables efficient stock keeping for the healthcare institution.
Keywords: preoperative templating software; total hip replacement; collarless polished tapered stem; preoperative planning